Development of Muslim friendly audit checklist for agro-based homestay spatial organization - Adib Azman (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2020)
Homestay concept can be defined as the owner of the house hosting the guests by providing all the needs. The homestay program is a genuine idea of local rural community in searching for additional source of income. It can be traced back from the early 1970s where the homestay program started at Kampung Cherating Lama, Kuantan. In 1995, the program has been officially established under MOTAC and presently homestay program has become one of the official tourism activities. With an opportunity to elevate the economic status of local rural community, homestay program appeared to be more distinct compared to other accommodation. However, the current situation of local homestay program in term of fulfilling the concept of Muslim friendly accommodation is still unclear. Therefore further assessment is needed to assess the practicality of shari'ah compliance inside and outside of homestay provider houses. The research aimed to develop Muslim friendly Audit Checklist for local agro-based homestay guideline which will lead to further understanding of the spatial organization and elements distribution inside and outside of the house. In order to execute the aim, three objectives have been constructed namely; 1) to identify the spatial organization and elements distribution for indoor and outdoor spaces of local agro-based homestay, 2) to assess the spatial organization and elements distribution of local agro-based homestay as according to Muslim friendly approach and 3) to construct Muslim friendly audit checklist for local agro-based homestay program. The data collection started with preliminary study on agricultural homestay by reviewing existing articles and journals. From the review, a preliminary checklist has been constructed as an instrument for data collection on sites to ensure the comprehensive coverage. From the literature review of several documents including academic articles, guidelines and standards, there are nineteen elements found that need to be covered in Muslim friendly homestay. Through observation and semi structured interview with the house owner, the preliminary checklist is further examined for improvement. The study is conducted at three different villages in three different region which practicing agricultural activities. The sites are selected based on the authenticity and type of activities conducted. From the data analysis, it can be found that the element of providing privacy for male and female is the most difficult element to comply. Among other elements that homestay providers failed to comply the most are provision of female prayer garments, a copy of al-Quran and prayer time information. All in all, the proposed audit checklist was verified by the experts through the discussion during one-on-one interview session. The suggestions from the experts were taken into consideration and the updated checklist was constructed. The construction of the audit checklist is expected to be the key towards the improvement of the organization of the spaces and elements distribution inside and outside of the houses in order to fulfill the needs of Muslim guests. Also the audit checklist can lead to the establishment of an official rating system for local homestay.